Toward an open access genomics database of South Africans: ethical considerations - Gooden, Amy; Thaldar, Donrich (Frontiers in Genetics, 2023)
Genomics research holds the potential to improve healthcare. Yet, a very low percentage of the genomic data used in genomics research internationally relates to persons of African origin. Establishing a large scale, open access genomics database of South Africans may contribute to solving this problem. However, this raises various ethics concerns, including privacy expectations and informed consent. The concept of open consent offers a potential solution to these concerns by (a) being explicit about the research participant’s data being in the public domain and the associated privacy risks, and (b) setting a higher-than-usual benchmark for informed consent by making use of objective assessment of potential research participants’ understanding. Furthermore, in the South African context—where local culture is infused with Ubuntu and its relational view of personhood—community engagement would be vital for establishing and maintaining an open access genomics database of South Africans. The South African National Health Research Ethics Council is called upon to provide guidelines for genomics researchers—based on open consent and community engagement—on how to plan and implement open access genomics projects.